DEVELOPMENT OF COLLABORATIVE PROBLEM SOLVING-BASED LEARNING TOOLS TO IMPROVE MATHEMATICAL ADAPTIVE REASONING SKILLS - Nunu Nurhayati; Yaya Sukjaya Kusumah; Dadang Juandi (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Students' ability to solve mathematical adaptive reasoning problems is still relatively low. As a result, students have difficulty in solving mathematical adaptive reasoning problems. The cause of the low mathematical adaptive reasoning ability of students is the lack of learning tools that facilitate mathematical adaptive reasoning ability. Therefore, a Collaborative Problem Solving-based tool was developed that can stimulate an active learning process, motivate students and improve mathematical adaptive reasoning skills. This research is a development research using the Plomp development model. The products developed are lesson plans and worksheets based on Collaborative Problem Solving for class VIII junior high school statistics material. The purpose of this research is to produce Collaborative Problem Solving-based tools that are valid, practical, and effective on the mathematical adaptive reasoning skills of grade VIII junior high school students. The results showed that the learning tools in the form of lesson plans and LKS based on Collaborative Problem Solving for students in grade VIII junior high school were valid, practical, and effective. The results of the validation of the learning tools developed are very valid, adjusting 5 indicators of mathematical adaptive reasoning skills seen from the aspects of making conjectures, providing reasons for the answers given, drawing conclusions from a statement, checking the validity of an argument, and finding patterns from a mathematical problem. The results of the practicality of learning devices are very practical in terms of ease of use, suitability of time allocation, attractiveness and usefulness. Furthermore, it is said to be effective because it has an impact on students' mathematical adaptive reasoning ability of 82.70% with a very good category.